The Color of Childhood: The Role of the Child/Human Binary in the Production of Anti-Black Racism. (May 2018) - Rollo, Toby
The binary between the figure of the child and the fully human being is invoked with regularity in analyses of race, yet its centrality to the conception of race has never been fully explored. For most commentators, the figure of the child operates as a metaphoric or rhetorical trope, a non-essential strategic tool in the perpetuation of White supremacy. As I show in the following, the child/human binary does not present a contingent or merely rhetorical construction but, rather, a central feature of racialization. Where Black peoples are situated as objects of violence it is often precisely because Blackness has been identified with childhood and childhood is historically identified as the archetypal site of naturalized violence and servitude. I proceed by offering a historical account of how Black peoples came to inherit the subordination and dehumanization of European childhood and how White youth were subsequently spared through their partial categorization as adults.